Neuropeptide-w protects against stress-induced gastric ulcer in rats via the involvement of capsaicin-sensitive vagal afferent fibers - PEKER EYÜBOĞLU, İREM; AKKİPRİK, MUSTAFA; YEGEN, BERRAK; AKAKIN, DİLEK (My University, 2020)
AIM: Neuropeptide-W (NPW), expressed in hypothalamus and peripheral organs, activates hypothalamus-pituitary-adrenal axis, and may have a physiological role in neuroendocrine response to stress. The aim was to evaluate protective effects of NPW on stress-induced gastric injury in rats. METHODS: Sprague-Dawley male rats were fasted for 24 hours, restrained and immersed in water-bath for 6 h to induce water-immersion restraint stress (WIRS), and NPW (0.1 or 5µg/kg) or saline was injected subcutaneously at 15 minutes before WIRS (n=24), while saline-injected control rats had no WIRS (n=8). For degeneration of vagal afferent fibers (VAD), in some rats (n=24) capsaicin (1%) was applied perivagally under ketamine anesthesia, and 3 weeks later WIRS was induced. Using a laser Doppler, gastric serosal blood flow was monitored under anesthesia. Following cardiac puncture, gastric tissues were removed for macroscopic/microscopic scoring and measurement of myeloperoxidase activity, malondialdehyde and glutathione levels. Gastric NF-κB and cerebral NPW mRNA expressions were detected by RT-PCR. One-way ANOVA was used for statistical analysis. RESULTS: WIRS decreased mean serosal blood flow, resulted in elevated macroscopic/ microscopic scores compared to control group (p<0.001), while myeloperoxidase activity and malondialdehyde level were elevated (p<0.05) and antioxidant glutathione was depleted (p<0.001). WIRS depressed gastric NF-κB and cerebral NPW mRNA expressions (p<0.01). Neither doses of NPW changed gastric NF-κB mRNA. Lowerdose of NPW elevated blood flow (p<0.001), abolished WIRS-induced elevations in myeloperoxidase and malondialdehyde levels (p<0.05). High-dose NPW replenished gastric glutathione and brain NPW expression and reduced scores (p<0.05-0.01). Despite that VAD did not alter effects of high-dose NPW, reductions in malondialdehyde and myeloperoxidase, and improvement in blood flow by low-dose NPW were abolished by VAD (p<0.05). CONCLUSION: In stress-induced oxidative gastric injury, NPW provides gastroprotection by improving depressed blood flow and inhibiting ulcer-induced oxidative injury, which involve contribution of vagal afferent fibers
Keywords: Neuropeptide-W; gastric ulcer; waterimmersion restraint stress; oxidative damage; inflammation